2020
DOI: 10.33774/apsa-2020-70b55
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loyal to the Executive: The Effect of State Capacity on Local Horizontal Accountability

Abstract: The literature suggests that state capacity has a reinforcing effect on democracy. According to this literature, the capacity and usability of the bureaucracy that state capacity entails are essential for the provision of goods and services that help to consolidate and improve democratic regimes. This paper challenges this proposition. It focuses on local democracy and draws on the comparative method to describe and evaluate how bureaucratic capacity and usability can affect a critical component of democracy-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Additionally, mayors may use fiscal rents to engage in informal practices, such as patronage and clientelism. Regarding patronage, research has shown that mayors' discretion over public employment has led them to use municipal hiring as a strategy for voter mobilization and to build a support base (Corvalan et al 2018;Došek 2019;Ordóñez 2023). Although there are certain legal restrictions that limit public employment, these only establish the maximum percentages of the municipal revenues-which include the FCM-that can be spent to hire municipal bureaucrats.…”
Section: Local Governments and Nontax Revenue In Chilementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, mayors may use fiscal rents to engage in informal practices, such as patronage and clientelism. Regarding patronage, research has shown that mayors' discretion over public employment has led them to use municipal hiring as a strategy for voter mobilization and to build a support base (Corvalan et al 2018;Došek 2019;Ordóñez 2023). Although there are certain legal restrictions that limit public employment, these only establish the maximum percentages of the municipal revenues-which include the FCM-that can be spent to hire municipal bureaucrats.…”
Section: Local Governments and Nontax Revenue In Chilementioning
confidence: 99%
“…For instance, Barozet (2008) shows that they offer employment and housing to boost their probability of success. Similarly, Pribble (2015) notes that mayors use the Municipal Labor Intermediation Office to claim credit for ensuring employment opportunities, whereas Ordóñez (2023) finds that mayors provide public resources to municipal councilors in exchange for loyalty, thereby undermining local horizontal accountability. Likewise, Došek's 2019 study of subnational democracy in Chile shows that less-than-democratic mayors build a strong support base mainly by delivering private goods to their constituents and local social organizations.…”
Section: Local Governments and Nontax Revenue In Chilementioning
confidence: 99%